2012
DOI: 10.1186/1472-6963-12-127
|View full text |Cite
|
Sign up to set email alerts
|

The acceptability, feasibility and impact of a lay health counsellor delivered health promoting schools programme in India: a case study evaluation

Abstract: BackgroundStudies in resource-limited settings have shown that there are constraints to the use of teachers, peers or health professionals to deliver school health promotion interventions. School health programmes delivered by trained lay health counsellors could offer a cost-effective alternative. This paper presents a case study of a multi-component school health promotion intervention in India that was delivered by lay school health counsellors, who possessed neither formal educational nor health provider q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 22 publications
0
49
0
Order By: Relevance
“…A study that conducted mass vision screenings in 51 Indian schools at the start of each academic year was identified as a cost–effective intervention 63 . Many studies noted the availability of uncomplicated referral pathways between education and health systems, and clarity regarding referral processes, as being crucial in successful follow-up, provision of spectacles and continuity of care 20 , 22 , 23 , 29 , 32 , 33 , 41 , 51 , 61 , 64 . For example, a study exploring children as potential vision screeners found that, despite being effective screeners, they were not held with sufficient credibility when referring those they screened to other health services 57 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A study that conducted mass vision screenings in 51 Indian schools at the start of each academic year was identified as a cost–effective intervention 63 . Many studies noted the availability of uncomplicated referral pathways between education and health systems, and clarity regarding referral processes, as being crucial in successful follow-up, provision of spectacles and continuity of care 20 , 22 , 23 , 29 , 32 , 33 , 41 , 51 , 61 , 64 . For example, a study exploring children as potential vision screeners found that, despite being effective screeners, they were not held with sufficient credibility when referring those they screened to other health services 57 .…”
Section: Resultsmentioning
confidence: 99%
“…Inappropriate or overprescribing of spectacles was identified in studies from India and Mexico, 26 , 43 suggesting that the prescribing of spectacles for moderate vision impairment should be balanced with cost and willingness to pay 43 . Overarching factors in the provision of successful school-based eye-care interventions included communication between health services and schools, the willingness of schools to schedule sufficient time while minimizing impact, 52 , 63 and the support of principals, staff and parents 23 , 28 , 29 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations